Impacts of sulfamethoxazole stress on vegetable growth and rhizosphere bacteria and the corresponding mitigation mechanism - Ren, Jiawei; Lu, Hongbin; Lu, Shaoyong; Huang, Zhanggen (Frontiers in Bioengineering and Biotechnology, 2024)
Antibiotics are an important pharmaceutical class excessively used by humans.Its presence in the soil can impact plant growth and induce antibiotic resistance. This research studies the effect of sulfamethoxazole (SMX) on plant growth, rhizosphere bacteria composition, and resistance genes. Two sets of vegetables (basil, cilantro, and spinach) were treated separately with water and SMX solution. The plant growth data and soil samples were collected and analyzed. The results revealed that SMX increased spinach leaf length (34.0%) while having no significant impacts on basil and cilantro. On the other hand, SMX improved the bacterial diversity in all samples.The shifts in the abundance of plant growth-promoting bacteria could indirectly affect vegetable stem and leaf length. SMX also significantly increased the abundance of resistance genes Sul1 and Sul2. A further study into the correlation between bacteria highlights the importance of Shingomonas and Alfipia for inhibiting the spread of key resistance gene hosts, namely Pseudomonas, Stenotrophomonas, and Agrobacterium.This research provides insight into SMX's impact on vegetable growth and microbial diversity. It also points out important microbial interactions that could potentially be utilized to mitigate ARG proliferation.